Approaching Fäerie: a study of J. R. R. Tolkien’s on fairy-stories - da Rocha, Fabian Quevedo (Revista PHILIA | Filosofia, Literatura & Arte, 2019)
This article discusses J.R.R. Tolkien's understanding of fantasy as a literary genre in light of his essay On Fairy Stories. It addresses key concepts of the essay that are of great importance for a broader understanding of the author's creative process and his views on the importance of fantasy stories for society. Among the concepts discussed in this analysis are Tolkien's ideas of sub-creation, secondary world, inner consistency of reality, as well as his views on Recovery, Escape, and Consolation, which he believed to be the main functions of fantasy. Finally, the concept of Fäerie, which is probably the most important term in the author's lexicon and key to his theory and practice, is also discussed in this work. Keywords: Fäerie. Fantasy Literature. J. R. R. Tolkien. On Fairy Stories.